Pengembangan Media Pembelajaran Pop-Up Book Digital pada Materi Bagian Tubuh Tumbuhan untuk Kelas IV SDN 44 Ampenan - Andiani Rachmawati; Ida Ermiana; Hasnawati (Mataram University, 2026)
Learning media innovation plays a crucial role in transforming conventional learning processes to be more dynamic and relevant to the characteristics of digital-generation students. The development of this Digital Pop-Up Book media is expected to create a more attractive, interactive, and meaningful learning experience to facilitate the understanding of abstract concepts, ultimately leading to an increase in student learning outcomes. This study aims to develop Digital Pop-Up Book media for fourth-grade Science and Social Studies (IPAS) subject that has been tested for its validity, practicality, and effectiveness. This study employed the Research and Development (R&D) method using the ADDIE model, which comprises five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 27 fourth-grade students at SDN 44 Ampenan. Data collection techniques were carried out through interviews, questionnaires, and tests. The validation results indicated that the media obtained a percentage of 91.67% from material experts and 98.3% from media experts, placing it in the highly valid category. Furthermore, the teacher response questionnaire reached a percentage of 88.3%, and the student response reached 86%, falling into the highly practical category. The students' average pre-test score of 52.59 increased to 82.59 in the post-test. The Wilcoxon Signed Rank Test results showed a significance value of 0.000 < 0.05, interpreting that there was a significant difference or improvement in students' IPAS learning outcomes before and after being given treatment using the new media. Meanwhile, the N-Gain test results yielded a score of 0.659 or 66%, categorized as moderate. These results demonstrated that the Digital Pop-Up Book media is moderately effective in improving the IPAS learning outcomes of fourth-grade students at SDN 44 Ampenan. Thus, it can be concluded that the Digital Pop-Up Book media is declared highly valid, highly practical, and moderately effective for use in learning the material on plant body parts